(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article studies the remarkable case of diplomatic asylum given by Mexican State to a Dominican politician who suffered persecution; this asylum was given in three different occasions in the mid-twentieth century. The research deals with the repressive situation that was characterized under the dictatorship of Rafael Leonidas Trujillo in the Dominican Republic. It examines the benefits and the narrow circumstances of the Convention on Latin American asylum. It emphasizes on the Mexican Asylum policies and the Mexican officials that put them into practice. It shows that there is a well-defined policy which is shaped by individual appreciation, professional attitude and the political will of those who put it into practice. With the above, this paper attempts to promote in a higher and better scale of knowledge such an important matter as it is itself the diplomatic Mexican foreign asylum policy shaped by the Latin American context.